Improving the Quality of Technical Vocational Education and Training (TVET) For Sustainable Growth and Development of Nigeria - Igberaharha, Clever Omovigho (Journal of Education and e-Learning Research, 2021)
This study was undertaken towards improving the quality of Technical Vocational Education and Training (TVET) at the university level for the sustainable growth and development of Nigeria. Two research questions guided the study, and two null hypotheses were tested. The design of the study was a descriptive survey with a population of 116 respondents. These TVET lecturers were drawn from five universities in the South-South region of Nigeria. The entire population was used for the study. To collect pertinent data for the study, the researcher developed a 20-item questionnaire. Face and content validity of the questionnaire was determined by three experts. In order to establish the reliability of the instrument, Cronbach Alpha was used, which gave a reliability coefficient of 0.86. Mean was used to analyze the data relating to the research questions while Pearson product moment correlation coefficient was used to test the null hypotheses. The study found that the quality of TVET at the university level can be improved, for the sustainable growth and development of Nigeria, through professional manpower and the provision of efficient facilities and equipment. Also, the study findings indicated a significant relationship between the quality improvement of TVET and the sustainable growth and development of Nigeria. It was recommended that TVET providers, policymakers, stakeholders, and governments in Nigeria should ensure ‘Education for Sustainable Development’ is fully integrated into the TVET program to ease the national development of the Nigerian economy.